Cellular immune responses against the cancer-testis antigen SPAN-XB in healthy donors and patients with multiple myeloma - Frank, Christian; Hundemer, Michael; Ho, Anthony Dick; Goldschmidt, Hartmut; Witzens-Harig, Mathias (Leukemia and lymphoma, 2008)
The cancer-testis antigen SPAN-XB has been recently identified in multiple myeloma (MM). In the present study, we identified and characterized for the first time a cytotoxic cellular immune response against SPAN-XB in healthy donors and patients with MM. Using two independent computer algorithms, two SPAN-XB-derived peptides (peptides 624 and 626) with predicted binding to HLA-A2 were identified. To further improve the immunogenicity of peptide 626 we designed a heteroclitic peptide (peptide 627) by modifying one amino acid on the HLA binding position 2 of peptide 626. Using an IFN-γ Elispot assay we could demonstrate the presence and functional activity of CD8 peptide specific T cells with all tested peptides. By analysis of peripheral blood of 13 healthy donors and five patients with MM peptide specific T-cell precursors specifically recognizing at least one of the tested peptides could be detected and expanded in 9 of 13 of tested donors and 3 of 5 tested patients. Importantly, in two donors specific peptides could be generated against the heteroclitic peptide 627 but not against the native peptide 626. We conclude that SPAN-XB-derived peptides can elicit a consistent CD8 T cell response in healthy donors and patients with MM.